Law, necropolitics and the stop and search of young people. (May 2020) - Flacks, Simon
Stop and search can harm young people, damage relations between police and the community and alienate ethnic and racial minorities. In Mohidin and another v Commissioner of the Police of the Metropolis and others, a group of minors who had been stopped, searched and, in some cases, falsely imprisoned, assaulted and racially abused by officers, were awarded damages for the distress and pain suffered. In this article, the case will be read not for the tortious legal consequences of police actions towards youth, or members of the public in general, nor for the culpability of any of the parties concerned, but for how the use of 'lawful' police powers on young people was framed and justified by both officers and the courts. It is argued that the punitive function of such powers has been underexplored by criminologists, and that the authorization and legitimization of such tactics, routinely defended as a 'necessary' crime prevention tool, can be understood as an instantiation of 'necropolitics'.